Dual energy X-ray absorptiometry positioning protocols in assessing body composition: A systematic review of the literature. Issue 10 (October 2018) - Shiel, Flinn; Persson, Carl; Furness, James; Simas, Vini; Pope, Rodney; Climstein, Mike; Hing, Wayne; Schram, Ben
Abstract: Objectives: To systematically identify and assess methods and protocols used to reduce technical and biological errors in published studies that have investigated reliability of dual energy X-ray absorptiometry (DXA) for assessing body composition. Design: Systematic review. Methods: Systematic searches of five databases were used to identify studies of DXA reliability. Two independent reviewers used a modified critical appraisal tool to assess their methodological quality. Data was extracted and synthesised using a level of evidence approach. Further analysis was then undertaken of methods used to decrease DXA errors (technical and biological) and so enhance DXA reliability. Results: Twelve studies met eligibility criteria. Four of the articles were deemed high quality. Quality articles considered biological and technical errors when preparing participants for DXA scanning. The Nana positioning protocol was assessed to have a strong level of evidence. The studies providing this evidence indicated very high test–retest reliability (ICC 0.90–1.00 or less than 1% change in mean) of the Nana positioning protocol. The National Health and Nutrition Examination Survey (NHANES) positioning protocol was deemed to have a moderate level of evidence due to lack of high quality studies. However, the available studies found the NHANES positioning protocol had very high test–retest reliability. Evidence is limited and reported reliability has varied in papers where no specific positioning protocol was used or reported. Conclusions: Due to the strong level of evidence of excellent test–retest reliability that supports use of the Nana positioning protocol, it is recommended as the first choice for clinicians when using DXA to assess body composition.